2018
DOI: 10.1007/s10886-018-0988-3
|View full text |Cite|
|
Sign up to set email alerts
|

Ritualised Dung Kicking by White Rhino Males Amplifies Olfactory Signals but Reduces Odour Duration

Abstract: Many mammals enhance their olfactory signals visually by depositing them in conspicuous locations such as well-travelled paths. It is also possible to enhance the odour itself through behaviours aimed at modifying odour emission rates. White rhinos defecate in communal middens. While defecating, territorial males kick sharply with their back feet which disperses their dung. Despite being a ubiquitous trait of territorial male white rhinos, the reason behind this behaviour is unclear. We hypothesised that the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Our EAG results showed strong dung beetle responses to ρ-cresol, 1H-indole, and skatole, but also suggested that other compounds, such as nonanal, acetophenone, and ρ-cymene, may also be involved in a ‘ generalized dung bouquet ’. Acetophenone, which was only identified in horse dung in our study, has previously been identified in dung samples of cows (Laor et al 2008 ), pigs (Blanes-Vidal et al 2009 ), and several wild vertebrates (Apps et al 2012 ; Marneweck et al 2017 ; Martín et al 2010 ; Stahl et al 2015 ), indicating that this may also be a general component of dung. Other electrophysiological and behavioral studies on dung beetles have shown the importance of compounds such as ρ-cresol, indole, and skatole in dung beetle responses (Frank et al 2018b ; Inouchi et al 1988 ; Shibuya and Inouchi, 1982 ; Weithmann et al 2020 ).…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Our EAG results showed strong dung beetle responses to ρ-cresol, 1H-indole, and skatole, but also suggested that other compounds, such as nonanal, acetophenone, and ρ-cymene, may also be involved in a ‘ generalized dung bouquet ’. Acetophenone, which was only identified in horse dung in our study, has previously been identified in dung samples of cows (Laor et al 2008 ), pigs (Blanes-Vidal et al 2009 ), and several wild vertebrates (Apps et al 2012 ; Marneweck et al 2017 ; Martín et al 2010 ; Stahl et al 2015 ), indicating that this may also be a general component of dung. Other electrophysiological and behavioral studies on dung beetles have shown the importance of compounds such as ρ-cresol, indole, and skatole in dung beetle responses (Frank et al 2018b ; Inouchi et al 1988 ; Shibuya and Inouchi, 1982 ; Weithmann et al 2020 ).…”
Section: Discussionsupporting
confidence: 61%
“…This compound has been found in several dung types, including dog, white rhino, red deer, wild boar, fox, and sheep (Arnould et al 1998 ; Dormont et al 2010 ; Frank et al 2018b ; Marneweck et al 2018 ). The compound 6-methyl-5-hepten-2-one, absent in rabbit dung, has been identified in various other dungs (Marneweck et al 2017 ; Murphy et al 2012 ; Raman et al 2013 , see also Goodrich et al 1981 ). Rabbit dung was the most chemically distinctive, with several exclusive VOCs, such as the monoterpenes camphene, 1,8-cineole, and verbenone (Table 2 ) (see Couch et al 2015 ; Marneweck et al 2017 ; Pillai et al 2010 ; Raman et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the fact that the elephants in our study were able to detect water olfactorily opens the possibility that they, especially with their exceptional sense of smell (Niimura et al 2014;Shoshani and Foley 2000;Shoshani et al 2006), may be able to detect water sources at distances beyond their visual range. Moreover, the VOC's being given off by the larger surface area of a body of water would likely be greater than those emitted from the small surface area of the beakers we used in our experiment (Aydin et al 2014;Marneweck et al 2018).…”
Section: Discussionmentioning
confidence: 99%